Carbonate system data tracing freshwater inflow into the Ross Sea through the eastern gate and along the Ross Ice Shelf (Antarctica) - Rivaro, Paola; Vivado, Davide; Castagno, Pasquale; Falco, Pierpaolo; Zambianchi, Enrico; Ianni, Carmela (Frontiers in Marine Science, 2022)
The eastern Ross Sea is a key area to understand the role of the Amundsen Sea inflow of freshwater that can influence the Ross Sea water properties and salt budget. A survey was carried out in the eastern Ross Sea during the austral summer 2019–20 to evaluate the contribution of the Amundsen Sea Water (ASW) to the salinity variability. A total of 248 seawater samples were collected fthe analysis of total alkalinity (AT) and pH. The data collected were used together with temperature and salinity to obtain a full description of the carbonate system properties including total inorganic carbon (CT), CO2 partial pressure (pCO2), calcium carbonate saturation state of aragonite and calcite (Ω), and Revelle factor. Moreover, we estimated the anthropogenic carbon (Cant) throughout the TrOCA method to better understand the carbon cycle, also considering the effect of atmospheric CO2 uptake on ocean acidification. We used principal component analysis (PCA) to investigate the major controls on the carbonate system parameters with the aim of defining their sensitivity as chemical tracers. The changes in carbonate chemistry in surface waters were mainly due to the physical properties. AT and pH traced the entry of the ASW showing limited mixing between water masses on the shelf area. Shelf waters were enriched in Cant, which resulted lower than the estimated value for shelf waters produced in western Ross Sea.